2007
DOI: 10.1007/s10637-007-9097-9
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of ispinesib (SB-715992) in patients with metastatic or recurrent malignant melanoma: a National Cancer Institute of Canada Clinical Trials Group trial

Abstract: To assess the response rate and toxicity of the kinesin spindle protein (KSP) inhibitor, ispinesib, in malignant melanoma. Seventeen patients were enrolled from April to November 2005. Ispinesib was administered as a 1-hour infusion at a dose of 18 mg/m2 once every 3 weeks until disease progression. No objective responses were seen. Six patients (35%) had a best response of stable disease for a median duration of 2.8 months. Disease progression was documented in 9 (53%) after 1 or 2 cycles. Eighty-eight percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 28 publications
3
45
0
Order By: Relevance
“…In this study, no conclusive evidence of benefit was seen with ispinesib monotherapy. Similar results were obtained from the phase II study in patients with metastatic or recurrent malignant melanoma (44). Although KSP expression seems to be common in melanoma and KSP would be an appropriate target for inhibition, no significant responses were observed in response to ispinesib and further development in malignant melanoma is not recommended.…”
Section: Clinical-translational Advancessupporting
confidence: 77%
“…In this study, no conclusive evidence of benefit was seen with ispinesib monotherapy. Similar results were obtained from the phase II study in patients with metastatic or recurrent malignant melanoma (44). Although KSP expression seems to be common in melanoma and KSP would be an appropriate target for inhibition, no significant responses were observed in response to ispinesib and further development in malignant melanoma is not recommended.…”
Section: Clinical-translational Advancessupporting
confidence: 77%
“…In mousebased xenograft models, Ispinesib inhibits tumour growth, and encouragingly, monopolar spindles were evident in tumour biopsies, indicating that KSP was targeted in vivo. Importantly, in Phase I clinical trials with Ispinesib and two other KSP inhibitors, namely SB-743921 and MK-0731, neuropathy was not reported as a major side effect; as expected for a cytotoxin, the dose limiting toxicities were neutropenia [16][17][18]. Thus, the KSP inhibitors appear to have achieved one major goal, namely the elimination of neurotoxicities.…”
Section: Ksp Inhibitors-bringing the Antimitotic Concept Into The 21smentioning
confidence: 85%
“…Multiple clinical studies on the antitumor activity of ispinesib confirmed the absence of significant neuro-and gastrointestinal toxicities, which makes ispinesib favorable over other mitotic spindle interfering drugs. Several phase I clinical trials (30)(31)(32) and at least 4 phase II trials (33)(34)(35)(36) on the application of ispinesib in cancer treatment have been described in literature. The studies were conducted with a variety of dose and treatment schedules in multiple tumor types, making a good comparison between the trials difficult.…”
Section: Discussionmentioning
confidence: 99%